Analisis Potensi Youtube sebagai Upaya Meningkatkan Minat Mahasiswa dalam Belajar Matematika dan Berwirausaha: Analysis of YouTube's Potential as an Effort to Increase Student Interest in Learning Mathematics and Entrepreneurship - Istighfaris Rezki; Rospala Hanisah Yukti Sari (Tunas: Jurnal Pendidikan Guru Sekolah Dasar, 2023)
The majority of social media users accessing the Youtube platform cannot be separated from the advantages in it. The main advantage is the ease of accessing and uploading videos available on Youtube with the internet for free without any space and time limitations. The purpose of this study was to find out and describe student responses when using the resume method via YouTube social media in learning mathematics. The method used in this study is a descriptive qualitative method by collecting questionnaires from students taking mathematics courses. The results of the average percentage score of the overall student response to resuming videos on Youtube reached 80%. The data analysis used in this study is descriptive quantitative while to test the validity of the questionnaire with Pearson Correlation and the reliability of the questionnaire with Cronbach Alpha using SPSS. This shows that the student's response when the ethics of resuming videos on Youtube in mathematics learning is positive.